2016
DOI: 10.1124/mol.116.103804
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Modulation of Proton Channel Hv1 in Cancer Therapy: Future Perspectives

Abstract: The pharmacological modulation of the immunosuppressive tumor microenvironment has emerged as a relevant component for cancer therapy. Several approaches aiming to deplete innate and adaptive suppressive populations, to circumvent the impairment in antigen presentation, and to ultimately increase the frequency of activated tumor-specific T cells are currently being explored. In this review, we address the potentiality of targeting the voltage-gated proton channel, Hv1, as a novel strategy to modulate the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 224 publications
(354 reference statements)
0
15
0
Order By: Relevance
“…It is worth reiterating that Hv1 expression is not exclusive to phagocytes of myeloid lineage, as some groups have reported expression in B and T lymphocytes (Fernandez et al, 2016). In B cells, Hv1 has been shown to regulate the strength of BCR signaling (Capasso et al, 2010).…”
Section: Pathological Function Of Hv1 Channels Hv1 In Brain Aging and Age-related Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth reiterating that Hv1 expression is not exclusive to phagocytes of myeloid lineage, as some groups have reported expression in B and T lymphocytes (Fernandez et al, 2016). In B cells, Hv1 has been shown to regulate the strength of BCR signaling (Capasso et al, 2010).…”
Section: Pathological Function Of Hv1 Channels Hv1 In Brain Aging and Age-related Pathologymentioning
confidence: 99%
“…Several proton current inhibitors, such as 4-aminopyridine, amantadine, amiloride, D600, nicardipine, imipramine, DM, chlorpromazine, clozapine, haloperidol, and rimantadine have potentially indirect effects on Hv1 function, presumably by increasing intracellular pH (Shin et al, 2015). In particular, epigallocatechin-3-gallate might interfere with Hv1 channel activity by modifying the lipid bilayer structure (Seredenina et al, 2015;Fernandez et al, 2016). Additionally, a toxic peptide C6 was identified as a high potential Hv1 blocker with specificity and high affinity (Kd = 1 nM) (Tang et al, 2020).…”
Section: Proton Channel Blockersmentioning
confidence: 99%
“…Furthermore, AGAP showed strong anticancer effects, including the inhibition of stemness, epithelial-mesenchymal transition, migration, and invasion toward MCF-7 and MDA-MB-231 breast cancer cells [228]. It also inhibited the voltage-gated proton channel Hv1 [229], which has been investigated as a possible target for cancer therapy and has been extensively reviewed elsewhere [230]. Two studies on a third M. martensii peptide, BmKn2, indicated that this peptide could selectively induce apoptosis in cancerous human oral cells, while normal cells were affected to a much lesser extent [231,232].…”
Section: Anticancer Effectsmentioning
confidence: 99%
“…Furthermore, several studies suggested H V 1 channel might play a role in cancer, being involved in proliferation and metastasis of tumour cells (Wang et al, ; Wang, Li, Wu, Che, & Li, ; Wang, Wu, Li, Zhang, & Li, ; Wang, Zhang, & Li, ). It was proposed that blocking the H V 1 channel could be a promising approach in cancer therapy by modulating the immunosuppressive tumour micro‐environment and inducing tumour cell acidification (Fernandez, Pupo, Mena‐Ulecia, & Gonzalez, ). An earlier study showed that H V 1 channel inhibition promoted apoptosis of leukaemic Jurkat cells (Asuaje et al, ).…”
Section: Introductionmentioning
confidence: 99%